Apogossypolone Inhibits Cell Proliferation and Epithelial-Mesenchymal Transition in Cervical Cancer via Activating DKK3 - Li, Yuling; Qu, Jinfeng; Liu, Lu; Sun, Yu; Zhang, Junhua; Han, Sai; Zhang, Youzhong (Frontiers in Oncology, 2022)
Apogossypolone (ApoG2), a novel derivative of gossypol lacking of two aldehyde groups, exhibits anti-tumor effects. However, the mechanisms by which ApoG2 regulates cervical cancer (CC) cells remain unclear. In this study, we treated two CC cell lines (CaSki and HeLa) with an increasing concentration of ApoG2 for 24 h. Cell Counting Kit-8 (CCK-8) assay, colony formation assay, flow cytometry and transwell invasion assay were utilized to detect cell proliferation, apoptosis and invasion in vitro. We first observed that ApoG2 inhibited cell proliferation, invasion and epithelial-to-mesenchymal transition (EMT) process in CC cells, along with upregulation of Dickkopf Wnt signaling pathway inhibitor 3 (DKK3) in a dose-dependent manner. The immunohistochemistry confirmed the downregulation of DKK3 in tumor tissues. Moreover, DKK3 was correlated with FIGO stage and lymph node metastasis. Functionally, DKK3 overexpression significantly suppressed cell viability, colony formation and invasion, but promoted apoptosis in CaSki and HeLa cells. Overexpression of DKK3 upregulated the protein levels of cleaved caspase-3 and E-cadherin, but downregulated the protein levels of Bcl-2, N-cadherin and Vimentin. Furthermore, DKK3 knockdown reversed the suppressive effects of ApoG2 on CaSki cell proliferation, invasion and EMT markers, while DKK3 overexpression enhanced these effects. In addition, ApoG2 treatment inhibited CC xenograft tumor growth and upregulated the protein levels of DKK3, cleaved caspase-3 and E-cadherin. In conclusions, these findings suggested that ApoG2 could effectively inhibit the growth and invasion of CC cells at least partly by activating DKK3.